Symbolic of the Edict of Augustus from El Bierzo - Twarowska-Antczak, Emilia (Studia Europaea Gnesnensia, 2011)
The article demonstrates the symbolical character of an edict of emperor Augustus issued in Narbo in 15 BC, which concerned administrative and fiscal organization of the castella and gentes-civitates in the north-western part of the Iberian Peninsula. The starting point is the presentation of the significance of documents engraved in bronze based on literary and epigraphic sources.